MEMBANGUN KARAKTER POSITIF MAHASISWA MELALUI PENDIDIKAN KARAKTER DALAM MENGHADAPI TANTANGAN DI ERA MODERN - Wulandari, Rizki; Nasution, Atikah Rahmah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The modern era is marked by rapid technological advancements, characterized by the ease and speed with which information can be accessed. This condition requires students to possess intellectual intelligence in both academic and non-academic fields while maintaining positive character as a foundation for their attitudes and actions in daily life. The purpose of this study is to explore efforts to build students’ character through character education in facing the challenges of the modern era. This research employs a qualitative approach using a literature study method to analyze and collect various data from books, articles, and relevant reports. Character can be built and developed through character education in both academic and non-academic settings to foster positive traits such as self-concept, discipline, responsibility, independence, courage, and others. This study is expected to provide insights that building students’ positive character can be achieved through character education implemented in higher education institutions. Keyword: character education, positive character